Bridging The Gap: Financial Literacy As A Mediator In Women’s Investment Behaviour In India’s Fintech Era (International Journal of Environmental Sciences, 2025)
Background: Financial literacy has been accepted as a key determinant of women’s investment patterns particularly in the context of India. This paper shows that even with increased technological development and financial capital, women show diverse patterns of investment as determined by their socioeconomic and cultural factors.Aim: This paper looks at how financial literacy influences the investment decisions of women in India and the mediating impact of cultural and technological factors.Method: This study used a cross-sectional quantitative descriptive design in which purposive random sampling was used to recruit participants in the context of India. Questionnaires to the samples of women were administered to obtain data. The research hypothesis was tested using Structural Equation Modelling (SEM) means. Resultant analysis was done with the use of SPSS and Smart PLS.Findings: This study explored that financial literacy remarkably mediates the connection between investment behavior and major influencing factors including access to financial resources, technology adoption, financial awareness, and cultural norms. Furthermore, women with strong financial literacy illustrated high confidence in portfolio diversification and investment decisions.Conclusion: This study concludes that financial literacy improvement through policy initiatives and education is important for women's empowerment in investment decision-making. Additionally, addressing socioeconomic factors is important to increase economic growth and financial inclusion.